Monetary policy in a globalized economy : a practitioner's view - Mohan, Rakesh, 1948- (New Delhi ; New York : Oxford University Press, 2009)
With reference to India.
Includes bibliographical references and index.
Keywords: Monetary policy -- India; Banks and banking -- India; Globalization -- Economic aspects -- India